Transformasi Tafsir Di Nusantara sebagai Sumber Pembelajaran Kontekstual dalam Pendidikan Agama Islam - Wildan Alwi; Muhammad Furqon; Khadijah Khadijah; Muhammad Kamil Mukhtar; Atabik Luthfi; Siti Uswatun Hasanah (SAP (Susunan Artikel Pendidikan), 2025)
This study aims to examine and analyze how the transformation of interpretation in the Archipelago can be used as a source of contextual learning in Islamic Religious Education (PAI), especially in the Madrasah Aliyah (MA) Nurani Bogor environment. Interpretation as a science that bridges the understanding of the verses of the Qur'an plays an important role in the process of learning Islamic Religious Education. However, in practice, the learning of interpretation in schools, including at MA Nurani Bogor, is still dominated by a textual approach that does not sufficiently link the meaning of the verses to the social, cultural, and real-life contexts of students. Students often have difficulty in understanding the relevance of the messages of the Qur'an to contemporary issues because the approach used tends to be classical. The transformation of interpretation that has developed in the Archipelago actually has great potential as a source of more contextual learning. This study uses a qualitative approach with a case study method, which is carried out through learning observations, interviews with teachers and students, and documentation of learning materials. The results of the study showed an increase in students' understanding in interpreting interpretations, thus opening up opportunities for students to be more implementative and contextual in practicing the contents of the interpretation.